Attitudinal beliefs about suicidal behavior in health professionals in the emergency area in a public hospital in Lima, Peru - Yuncar-Fajardo, Diana; Gutiérrez Crespo, Hugo F; Matzumura Kasano , Juan P (Medicina Clínica y Social, 2023)
Introduction: Each year there are some 800,000 deaths by suicide, exceeding the number of people who die by homicide and wars throughout the world. In 2016, suicide was the second leading cause of death among people aged 15-29 worldwide. Objective. To describe attitudinal beliefs about suicidal behavior in health professionals in the emergency area of a public hospital. Methods. Quantitative, descriptive, and cross-sectional research. The population consisted of professionals who worked in the emergency department of a public hospital in Lima. A non-probabilistic convenience sample of 93 participants was used. The Attitudinal Beliefs Questionnaire on suicidal behavior, composed of four factors with a reliability of 0.87, was used. Results. 93 health professionals participated. The average age was 35.6 years. Factor 1: Legitimization of suicide and Factor 4: Suicide itself, showed attitudes of rejection of suicidal behavior, while Factor 2: Suicide in terminally ill patients and Factor 3: Morality of suicide, showed attitudes in favor. The scores in the four factors and in the total score of the questionnaire for the group of physicians and other professionals did not show significant differences. The 51.6% (n=48) belong to the 50th percentile, who have indifferent attitudes and beliefs for suicide and 34.7% (n=23) to the 75th percentile, who have attitudes and beliefs in favor of it. Discussion. Most of the participants showed neutral attitudes and beliefs for suicide. Attitudes in favor of suicide were only evident in the morale and terminally ill factors. Attitudinal beliefs for physicians and other health professionals showed no significant differences.
Keywords: Suicide; Attitude; personal health services